2009
DOI: 10.3892/or_00000659
|View full text |Cite
|
Sign up to set email alerts
|

Expression of neural stem cell markers in malignant rhabdoid tumor cell lines

Abstract: Abstract. Malignant rhabdoid tumor (MRT) is considered to display multi-phenotypic characteristics but the true origin of this tumor remains unknown. In recent years, the concept of the cancer stem cell (CSC) has drawn great attention. In the present study we investigated six MRT cell lines (TM87-16, STM91-01, TTC642, TTC549, YAM-RTK-1 and TTC1240), for CD133, nestin and Musashi-1 (Msi-1), which are considered to be CSC as well as neural stem cell (NSC) markers, using assays for cell viability and apoptosis, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Cell type may influence not only whether a mutation acts as driver, but also whether a driver gene appears to be an oncogene or a tumor suppressor (91). However, not all cancers have a known cell of origin; rhabdoid tumors, for instance, do not (92). Other mutations present in the model system used must also be considered.…”
Section: Functional Validation Of Candidate Driversmentioning
confidence: 99%
“…Cell type may influence not only whether a mutation acts as driver, but also whether a driver gene appears to be an oncogene or a tumor suppressor (91). However, not all cancers have a known cell of origin; rhabdoid tumors, for instance, do not (92). Other mutations present in the model system used must also be considered.…”
Section: Functional Validation Of Candidate Driversmentioning
confidence: 99%
“…Several studies have reported that nestin is a marker of CSCs in different malignancies [ 63 , 64 , 65 ]. CSCs represent a distinct population of undifferentiated cells responsible for tumor initiation and maintenance, and play a prominent role in the growth, migration, and invasion of neoplasms.…”
Section: Nestin-expressing Cells In Lung Cancermentioning
confidence: 99%